Integrating climate change vulnerability assessments from species distribution models and trait-based approaches. (October 2015) - Willis, S.G.; Foden, W.; Baker, D.J.; Belle, E.; Burgess, N.D.; Carr, J.A.; Doswald, N.; Garcia, R.A.; Hartley, A.; Hof, C.; Newbold, T.; Rahbek, C.; et al.
Abstract: To accommodate climate-driven changes in biological communities, conservation plans are increasingly making use of models to predict species' responses to climate change. To date, species distribution models have been the most commonly used approach for assessing species' vulnerability to climate change. Biological trait-based approaches, which have emerged recently, and which include consideration of species' sensitivity and adaptive capacity, provide alternative and potentially conflicting vulnerability assessments and present conservation practitioners and planners with difficult choices. Here we discuss the differing objectives and strengths of the approaches, and provide guidance to conservation practitioners for their application. We outline an integrative methodological framework for assessing climate change impacts on species that uses both traditional species distribution modelling approaches and biological trait-based assessments. We show how these models can be used conceptually as inputs to guide conservation monitoring and planning.